Controle químico de Fusarium moniliforme em sementes de milho: metodologia de avaliação e efeitos sobre a qualidade fisiológica - Moraes, Maria H. D. [UNESP]; Menten, José O. M. [UNESP]; Gravena, Jouse C. [UNESP]; Alves, Camila A. [UNESP] (Sociedade Brasileira de Fitopatologia, 2003)
The objectives of this study were to evaluate the effect of light regimes on the mycelial growth of Fusarium moniliforme in fungicide-amended culture medium; to select the best light regime to detect F. moniliforme in treated corn (Zea mays) seeds and the variable to be used; and the effect of treatment on seed health and physiological quality. The fungicides evaluated were: fludioxonil + metalaxyl-m (three concentrations), difenoconazole, acibenzolar-S-methyl e captan + thiabendazole. For evaluation of mycelial growth, fungicides were added to the culture medium at three concentrations (100, 10 and 11 æg/ml). Inoculated plates were incubated at 20±2 ºC, under three light conditions: total darkness, white light and near ultraviolet light (12 h of light/12 h of darkness). In order to evaluate the effect of light on fungicide-treated seeds, a deep freezing test was carried out and seeds were incubated under the same conditions as the former test; seed health test was evaluated by measuring disease incidence and severity. Two seed samples were treated and submitted to seed health, germination, seedling emergence rates in greenhouse and cold tests. In vitro tests indicated that white light decreased the effect of the active ingredients fludioxonil + metalaxyl-m and captan + thiabendazole. The health test did not show this effect. Severity of the disease was found to be the most sensitive variable to distinct efficacy of fungicides in controlling F. moniliforme in corn seeds. The results found for both the two seeds samples suggested that: a) Fusarium moniliforme does not affect the physiological quality of corn seeds; b) the fungicide that controlled the pathogen in seeds was captan + thiabendazole, followed by fludioxonil + metalaxyl-m (97.2 g + 147.86 g/l); c) Pythium sp. was controlled by captan + thiabendazole and by fludioxonil + metalaxyl-m at the three concentrations.

Objetivou-se verificar o efeito da luz sobre o crescimento micelial de Fusarium moniliforme em meio de cultura contendo fungicidas, o melhor regime luminoso e a variável a ser utilizada para detectar o patógeno em sementes tratadas de milho (Zea mays), e o efeito do tratamento sobre a qualidade sanitária e fisiológica das sementes. Os fungicidas avaliados foram fludioxonil + metalaxil-m (três concentrações), difenoconazole, acibenzolar-S-metílico e captan + tiabendazole. Para avaliação do crescimento micelial, os fungicidas foram adicionados em meio de cultura, nas concentrações de 100, 10 e 1 æg/ml. Incubaram-se as placas sob temperatura de 20±2 ºC e três condições de luz: escuro contínuo, luz branca e luz próxima da ultra violeta (12h de luz/12 de escuro). Para verificar o efeito da luz na avaliação das sementes tratadas, utilizou-se o método do papel de filtro com congelamento; a sanidade foi avaliada pelas variáveis incidência e severidade. Duas amostras de sementes tratadas foram submetidas aos testes de sanidade, germinação, emergência em casa de vegetação e frio, para verificar o efeito do tratamento sobre a qualidade sanitária e fisiológica. O teste in vitro indicou que a luz branca diminuiu o efeito dos ingredientes ativos fludioxonil + metalaxil-m (7,5 g + 11,51 g/l e 25 g + 10 g/l) e captan + tiabendazole; no teste de sanidade não se observou esse efeito. A severidade foi mais sensível para discriminar a eficiência dos fungicidas. Os resultados obtidos, avaliando-se as amostras de sementes tratadas, demonstraram que: F. moniliforme não afeta a qualidade fisiológica dessas sementes; o fungicida que ofereceu controle do patógeno na semente, acima de 90%, foi captan + tiabendazole, seguido de fludioxonil + metalaxil-m (97,2 g + 147,86 g/l); Pythium sp. foi controlado por captan + tiabendazole e por fludioxonil + metalaxil-m nas três concentrações.
Chemical control of Fusarium moniliforme in corn seeds: methodology of evaluation and effects on the physiological quality
Keywords: fungicidas; luz; germinação; vigor